After : the graphic novel. Volume one - Todd, Anna; Grisseaux, Veronique (After : the graphic novel, 2022)
"Tessa Young is a good girl with a sweet, reliable boyfriend back home. She's got direction, ambition, and a mother determined to keep her on course. But she's barely moved into her freshman dorm when she runs into Hardin Scott, with his tousled brown hair, cocky British accent, and tattoos. He's good looking, confident, and rather rude, even a bit cruel. For all of his attitude and insults, Tessa should hate Hardin, and she does--until something about his dark mood grabs her, and it's only a matter of time before he ignites a passion in her that she's never known before. He will call her beautiful, then insist he's not the one for her, making excuses and disappearing, again and again. He'll turn away from her, yet when she tries to push him aside, he'll only pull her in deeper. Despite the reckless way Hardin treats her, Tessa is drawn to his vulnerability and determined to unmask the real Hardin beneath all the lies"--Back cover.